Contractibility and Transparency of Financial Statement Information Prepared Under IFRS: Evidence from Debt Contracts Around IFRS Adoption - BALL, RAY; LI, XI; SHIVAKUMAR, LAKSHMANAN (Journal of Accounting Research, 2015)
ABSTRACT We outline several properties of IFRS that potentially affect the contractibility or the transparency of financial statement information, and hence the use of that information in debt contracts. Those properties include the increased choice among accounting rules IFRS gives to managers, enhanced rule‐making uncertainty, and increased emphasis on fair value accounting. Consistent with reduced contractibility of IFRS financial statement information, we find a significant reduction in accounting‐based debt covenants following mandatory IFRS adoption. The reduction in accounting covenant use is associated with measures of the difference between prior domestic standards and IFRS. Because IFRS adoption changed financial reporting in many ways simultaneously, it is difficult to trace the decline in accounting covenant use to individual IFRS properties, though we report larger declines in accounting covenant use in banks, which have a higher proportion of assets and liabilities that are fair‐valued. Our findings are better explained by reduced contractibility than by increased transparency, which would predict reduced nonaccounting covenant use as well, whereas we observe increases. Overall, we conclude that IFRS rules sacrifice debt contracting usefulness to achieve other objectives, such as provision of accounting information relevant to valuation.